Controllership Influences on the Restructuring of Slovenian Companies - Danijel Lebar; Iztok Kolar (Naše gospodarstvo/Our economy, 2015)
Controllership, as an informational activity, is becoming a multidimensional function, about which numerous doubts exist as to whether to increase its independency and integrate it tightly with the decision-making process. Financial knowledge and business-analytical capabilities of carriers of controllership activity can offer support for operational, financial, and strategic restructuring. This is important when facing frequent business dynamics in order to enhance competitiveness and especially achieve short-term as well as strategic goals.